Environmental Taxation: New Evidence for Energy Taxes - Maja Grdinić; Maja Klun; Žiga Kotnik (Central European Public Administration Review)
The intensity of exploitation of natural resources has increased over the past decades, making environmental protection policy one of the most important priorities of government institutions. Various economic instruments, including taxation, may help policy makers in the EU meet environmental targets, among them a more secure and competitive green economy in Europe. The focus of this paper is on empirically investigating the direct effect of environmental taxes and the indirect effect of environmental expenditures sourced from environmental taxes on greenhouse gas (GHG) emissions in the energy sector. The research applied the panel data analysis method to selected EU member states for the 1995–2010 period. The results show that the direct effect of environmental taxes on GHG emissions in the sector energy is statistically significant and negative. The indirect effects of environmental taxes resulting from environmental expenditures in the industrial and governmental sectors were found to be even stronger than the direct effect of taxes alone.